Preparation and Characterization of Manganese Ferrite Aluminates - R. L. Dhiman; S. P. Taneja; V. R. Reddy (Advances in Condensed Matter Physics)
Aluminum doped manganese ferrites MnAlxFe2−xO4 with 0.0≤x≤1.0 have been prepared by the double ceramic route. The formation of mixed spinel phase has been confirmed by X-ray diffraction analysis. The unit cell parameter `aO' is found to decrease linearly with aluminum concentration due to smaller ionic radius of aluminum. The cation distributions were estimated from X-ray diffraction intensities of various planes. The theoretical lattice parameter, X-ray density, oxygen positional parameter, ionic radii, jump length, and bonds and edges lengths of the tetrahedral (A) and octahedral (B) sites were determined. 57Fe Mössbauer spectra recorded at room temperature were fitted with two sextets corresponding to Fe3+ ions at A- and B-sites. In the present ferrite system, the area ratio of Fe3+ ions at the A- and B-sites determined from the spectral analysis of Mössbauer spectra gives evidence that Al3+ ions replace iron ions at B-sites. This change in the site preference reflects an abrupt change in magnetic hyperfine fields at A- and B-sites as aluminum concentration increases, which has been explained on the basis of supertransferred hyperfine field. On the basis of estimated cation distribution, it is concluded that aluminum doped manganese ferrites exhibit a 55% normal spinel structure.